The Association Between an Addictive Tendency Toward Food and Metabolic Characteristics in the General Newfoundland Population - Nelder, Matthew; Cahill, Farrell; Zhang, Hongwei; Zhai, Guangju; Gulliver, Wayne; Teng, Weiping; Shan, Zhongyan; Sun, Guang (Frontiers in Endocrinology, 2018)
Background: Our previous study of 29 obese food addiction (FA) patients found that FA is associated with lipid profiles and hormones which may be a factor in cardiovascular disease (CVD) and insulin resistance (IR). However, there is currently no data available regarding the relationship between FA symptoms and metabolic characteristics of CVD and IR in the general population. We designed this study to investigate the correlation between FA symptoms with lipid profiles and IR in men and women of the general Newfoundland population. Methods: 739 individuals (450 women & 289 men) recruited from the general Newfoundland population were used in analysis. FA symptoms were evaluated using the Yale Food Addiction Scale (YFAS). Glucose, insulin, HDL, LDL, total cholesterol and triglycerides levels were measured. IR was evaluated using the homeostatic model of assessment (HOMA). Participants were grouped by sex and menopausal status. Age, physical activity, calories and total % body fat were controlled. Results: Partial correlation analysis revealed that in men, YFAS symptom counts were significantly correlated with insulin (r=0.149 p=0.047), HOMA-IR (r=0.172 p<0.038), HOMA-β (r=0.173 p=0.036), triglycerides (r=0.204 p=.001) and inversely correlated with HDL (r= -0.147 p=0.015). In women there was a small correlation between YFAS symptoms and triglycerides (r=0.096 p=0.045). After separating by menopausal status, pre-menopausal women exhibited no correlation and post-menopausal women had a much higher correlation with triglycerides (r=0.249 p=0.002). Conclusion: FA is significantly correlated with several markers of metabolic disturbance in men and to a lesser extent, post-menopausal women, in the general population. Further research is required to explain sex specific associations and elucidate any potentially causal mechanisms behind this correlation.